Structures of Labor Inequality in the Main Mexican Avocado Enclave - Saldaña Contreras, José Luis (2025)
This study analyzes structural inequality in employment within the avocado agro-industrial enclave of Michoacán, Mexico. It examines income distribution asymmetries, labor segmentation mechanisms, and heterogeneity in contractual conditions, among other aspects. Through a mixed-methods research design, quantitative analyses (indices and coefficients) are integrated with qualitative evidence obtained from interviews and ethnographic observation. The findings indicate a concentration of surplus among large producers and traders, while a significant number of agricultural workers face labor precarity and limited access to formal employment and social security schemes. The study concludes that the agro-export specialization, structured as a productive enclave, has perpetuated structural inequalities and a dependency position, expressing the need for public policy interventions and other measures to reduce these disparities.